Sensitivity of palaeotidal models of the northwest European shelf seas to glacial isostatic adjustment since the Last Glacial Maximum. (1st November 2016) - Ward, Sophie L.; Neill, Simon P.; Scourse, James D.; Bradley, Sarah L.; Uehara, Katsuto
Abstract: The spatial and temporal distribution of relative sea-level change over the northwest European shelf seas has varied considerably since the Last Glacial Maximum, due to eustatic sea-level rise and a complex isostatic response to deglaciation of both near- and far-field ice sheets. Because of the complex pattern of relative sea level changes, the region is an ideal focus for modelling the impact of significant sea-level change on shelf sea tidal dynamics. Changes in tidal dynamics influence tidal range, the location of tidal mixing fronts, dissipation of tidal energy, shelf sea biogeochemistry and sediment transport pathways. Significant advancements in glacial isostatic adjustment (GIA) modelling of the region have been made in recent years, and earlier palaeotidal models of the northwest European shelf seas were developed using output from less well-constrained GIA models as input to generate palaeobathymetric grids. We use the most up-to-date and well-constrained GIA model for the region as palaeotopographic input for a new high resolution, three-dimensional tidal model (ROMS) of the northwest European shelf seas. With focus on model output for 1 ka time slices from the Last Glacial Maximum (taken as being 21 ka BP) to present day, we demonstrate that spatial and temporal changes in simulated tidal dynamics are very sensitive to relative sea-level distribution. The new high resolution palaeotidal model is considered a significant improvement on previous depth-averaged palaeotidal models, in particular where the outputs are to be used in sediment transport studies, where consideration of the near-bed stress is critical, and for constraining sea level index points. Highlights: Developed a new state-of-the-art palaeotidal model of the NW European shelf seas. Incorporates the most recent glacial isostatic adjustment model for the region. New outputs of tidal elevation amplitudes, phases and tidal-induced bed shear stress. Considerable differences in the tidal evolution in comparison to previous models. Choice of palaeotopography is more important than the choice of hydrodynamic model.